A case study of the English language teachers’ attitudes toward use of information and communication technology (ICT) in Finland - Zhelezovskaia, Iuliia (fi=Turun yliopisto|en=University of Turku|, 2016)
This qualitative study was aimed at investigating foreign language teachers’ attitudes toward use of information and communication technology (ICT) in their instruction. The insight was gained through the reported experience of ICT implementation by teachers, in what way and for which purpose they refer to use of technology, what kind of support and training they are provided with, and what beliefs they express about the influence of ICT implementation. This case study took place in one of the training schools in Finland. Five teachers participated in semi-structured interviews through a face-to-face approach. The findings demonstrated positive attitudes of teachers toward integration of ICT. The teachers shared their opinions about positive influence that ICT implementation has on both teaching and learning processes. However, they also pointed out the negative sides of ICT use: distraction of the students from usage of technology and technical problems causing frustration to the teachers. In addition, the responses revealed that the teachers are provided with adequate training aimed at enhancing their qualification which is provided with well-timed technology support and colleagues’ collaboration facilitating an efficient and smooth pace of the teaching process. According to the teachers’ opinions ICT integration in education appeared to have changed the role of the teacher. Due to different alterations in the field of ICT development teachers are required to upgrade their skills. The paper concludes with the limitations of the study and the recommendations for conducting further research.